PEMANFAATAN TEPUNG BUAH ALPUKAT (Persea americana Mill.) DALAM PEMBUATAN BOLU TERHADAP DAYA TERIMA DAN KANDUNGAN GIZINYA - Nurhalis Siregar; Zulhaida Lubis; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Food diversification efforts can be done by using local food. Avocado is one of the local food that have many nutrients and its availability is quite promising because the production of avocado tend to increase every year. Avocado processed into flour as substitute the wheat flour in the manufacture of cake. Avocado flour cake is one of the food product that modified by adding flour avocado and contain nutrient that needed the body. The purpose of this research is to know the acceptability of avocado flour cake based organoleptic analysis the taste, smell, color, and texture of avocado flour cake that determined using hedonic scale and to know protein and fat of avocado flour cake. This research is experimental research. Manufacture of avocado flour cake consists of two factors, they are wheat flour and avocado flour cake with 3 treatments. Each treatment use combination of avocado flour cake and wheat flour as much as 10%: 90%, 20%: 80% and 30%: 70% with symbol A1, A2, and A3. Panelist in this research are students of the Fakultas Kesehatan Masyarakat Universitas Sumatera Utara as many as 30 people. The results showed that the organoleptic test results avocado flour cake which is most favored based color is treatment III (A3) with score 78.9%, while avocado flour cake most favored based smell, texture, and taste is treatment I (A1) with each score 81.1%, 83.3% and 87.8%. Based the results of analysis fat and protein of avocado flour cake that highest fat is treatment III (A3) as much as 428 mg, while avocado flour cake that highest protein is treatment II (A2) as much as 135,4 mg. Suggested in order to can be done further research towards making avocado flour cake to improve the quality of acceptability and its nutrient content. Keywords : Avocado Flour, Avocado Flour Cake, Acceptability, Nutrient Content